Beyond incomes: What is the true impact of engaging in seed production on women's lives? Part 2. - Khan, Afreen; Puskur, Ranjitha; Tenneti, Suchaita (International Rice Research Institute, 2024)
Two Farmer Producer Companies (FPC) in Odisha, India aim to further sustain their increased yields and bridge productivity gaps by facilitating and activating women's entrepreneurship in paddy seed production. This blog is a part of IRRI’s 2024 International Women’s Day campaign.